2013
DOI: 10.1007/s13205-013-0148-y
|View full text |Cite
|
Sign up to set email alerts
|

Mycoremediation of Benzo[a]pyrene by Pleurotus ostreatus in the presence of heavy metals and mediators

Abstract: Benzo[a]pyrene is considered as a priority pollutant because of its carcinogenic, teratogenic and mutagenic effects. The highly recalcitrant nature of Benzo[a]pyrene poses a major problem for its degradation. White-rot fungi such as Pleurotus ostreatus can degrade Benzo[a]pyrene by enzymes like laccase and manganese peroxidase. The present investigation was carried out to determine the extent of Benzo[a]pyrene degradation by the PO-3, a native isolate of P. ostreatus, in the presence of heavy metals and lignin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Besides, mushrooms are also found to have the ability to biodegrade PAHs both in the absence (Lau et al, 2003;Lettera et al, 2010;Li et al, 2010) and in the presence of heavy metals (Atagana, 2009;Baldrian et al, 2000;Bhattacharya et al, 2013), as mushrooms could secrete extracellular enzymes, such as laccase, lignin peroxidase and manganese dependent peroxidase, a series of enzymes with the capacity to degrade and transform PAHs (Burns et al, 2013;Rao et al, 2014). That is to say, mushrooms might have a great potential to remediate the HM-PAHs co-contaminated soils.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, mushrooms are also found to have the ability to biodegrade PAHs both in the absence (Lau et al, 2003;Lettera et al, 2010;Li et al, 2010) and in the presence of heavy metals (Atagana, 2009;Baldrian et al, 2000;Bhattacharya et al, 2013), as mushrooms could secrete extracellular enzymes, such as laccase, lignin peroxidase and manganese dependent peroxidase, a series of enzymes with the capacity to degrade and transform PAHs (Burns et al, 2013;Rao et al, 2014). That is to say, mushrooms might have a great potential to remediate the HM-PAHs co-contaminated soils.…”
Section: Introductionmentioning
confidence: 99%
“…Pleurotus ostreatus is able to degraded Benzo[a]pyrene but the presence of heavy metal cations and mediators such as vanillin and 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonate) highly influence the degradation process. Bhattacharya et al, (2014), reported that 15 mM concentration of copper was found to best enhance the degradation (74.2%), progressively worsened as the Cu concentration increased. At the same time the extent of degradation was increased to 83.6 % when 5 mM of vanillin was included in the medium.…”
Section: Bioremediation Using Mushroommentioning
confidence: 98%
“…Production enhancement of MnP by some white rot fungus with MnSO4 has also been reported in some studies. However, each reported WRF has a different concentration tolerance in the presence of mineral inducer [7][16]. The second method is by increasing the solubility of BaP in the water based-liquid medium.…”
Section: Enhanced Culture System For Bap Degradation Using Mnso4 and mentioning
confidence: 99%